The future of Colorado forests: assessing seedling performance under climate change - Carroll, Charles Jeffrey Williamson, author; Knapp, Alan, advisor; Martin, Patrick, advisor; Bauerle, Bill, committee member; Brown, Peter, committee member (Colorado State University. Libraries, 2018)
Warming temperatures as a primary manifestation of climate change will dramatically alter the forests of the Rocky Mountain region as species will either adapt in place, migrate to suitable habitats, or face extirpation. Due to high levels of seedling local adaptation and covariance between temperature and precipitation in the Rocky Mountains, predictions of future tree performance are plagued by confounding variables leading to large uncertainties about how the principal drivers of climate will shape the forests of the future. To address this concern, I established three experimental gardens along a consistent temperature gradient with similar precipitation patterns at each garden in an effort to control the water inputs to these systems and address the role of temperature on seedling performance. This allowed me draw inference about how climate change will impact one of the most vulnerable age-classes of trees under real-world conditions. My dissertation focuses on the impacts of rising temperature on four of the dominant tree species of the Colorado Rocky Mountains, specifically focusing on how performance assessed from the physiological to the whole-plant level will be affected by investigating three main questions: (1) how are three critical anatomical, physiological, and phenological leaf traits impacted by 3°C to 6°C of warming? (2) How will warming impact whole-plant growth, prioritization of resources, and survivorship? (3) How will warming temperatures exacerbate water stress, and how plastic can the response be to that stress? In Chapter 2, I examine the impact of warming on leaf size, the temperature of optimal photosynthesis, and the timing of leaf bud burst to assess how plastic these traits are to warming. I found divergent patterns where the deciduous angiosperm performed best at the site closest in elevation to its local seed-source and declined performance with either warming or cooling, while the conifer species were less sensitive to ambient conditions. In Chapter 3, I focus on whole-plant growth, prioritization of growth to either height or basal area, and survivorship. I show that growth was unambiguously accelerated by warming across the gardens, favoring fast-growing angiosperm over the conifers. Each species preferentially allocated resources to basal area over height, an effect that accelerated with warming, and survivorship was largely attributed to stochasticity as no clear patterns between growth rate and survivorship were determined. Finally, in Chapter 4 I explored the water-stress conditions and plastic responses across the gardens focusing on osmotic adjustments and shifts in leaf structural components to tolerate water stress, however those shifts in resources necessary to tolerate unfavorable conditions may come at the expense of efficient growth. In sum, my dissertation highlights the importance of incorporating temperature directly into forecasts of seedling performance in the future by assessing their performance at different scales. Investigating seedling tolerance of warming at a single level of inference – be it at the physiological, anatomical, or whole-plant level – can lead to incomplete interpretations and predictions. I advocate for the expanded use of experimental gardens to isolate to the best degree possible the impacts of the main drivers of climate, and test using real-world conditions the impact of warming on tree seedlings in the future.
Keywords: ecophysiology; seedlings; climate change; temperature; growth